Minecraft - Monster, Sfé R. (Minecraft, 2019)
Tyler moves to a new city and away from his friends linked together through Minecraft. As Tyler adjusts to his new life, he logs back into Minecraft and meets all his old friends who have a surprise quest in store to welcome him back--to travel to the End and take on the ender dragon.